Kinetic Aspects of the Interaction of Blood Clotting Enzymes - Hemker, H. C; Hemker, P. W (Thrombosis and Haemostasis, 1968)
The enzyme kinetics of competitive inhibition under conditions prevailing in clotting tests are developed and a method is given to measure relative amounts of a competitive inhibitor by means of the t — D plot.